Listening for the Lex Orandi: The Constructed Theology of Contemporary Worship Events - Holmes, Stephen R. (Scottish journal of theology, 2013)
Scholarly attention to the popular style of contemporary worship has so far been infrequent, and generally dismissive. Dismissive attitudes have generally been based on claims that individual contemporary worship songs are lacking in theological development, and that contemporary worship merely apes the mores of pop culture, replacing a proper liturgical event with something akin to a rock concert. In this paper I suggest that both these criticisms are false. The first is a misunderstanding of the nature of the liturgical tradition of contemporary worship, in which the crucial liturgical event is the ‘time of worship’, constructed out of a number of songs and other liturgical elements, which together construct a liturgical narrative with theological and pastoral depth; criticising individual songs is therefore largely irrelevant. The second fails to pay attention to the nuanced negotiation with popular culture that is evident in the tradition of contemporary worship, when observed carefully; dominant cultural practices are not unreflectively adopted, but modified and, if embraced, embraced critically and put to use. I demonstrate these two points by offering readings of two (video recordings of) contemporary worship events, Matt Redman's Facedown DVD and Tim Hughes's Happy Day DVD; in each case I explore the ways in which cultural practices are modified and effectively subverted in pursuit of a liturgical goal, and offer a theological reading of the narrative of the time of worship. I propose that, whilst there are significant differences, both can be seen to be liturgically responsible and theologically deep experiences of worship.